Bilateral acute angle closure glaucoma caused by fluoxetine: a case report - Pina, S (2011)
Background: Acute angle closure glaucoma (ACG) occurs in patients with narrow iridocorneal angle, being more prevalent in elderly, hyperopic and asian. Mydriasis, induced by factors such as darkness, stress or drugs, may be a triggering factor of this disease. Methods: Case report of a 55 years old patient, female, black, with history of depressive mood that one month after initiation of oral fluoxetine therapy, appears in the emergency department with bilateral condition of intense eye pain, tearing, photophobia, decreased vision, nausea and vomiting. Ophthalmological exam showed corneal edema, conjunctival injection, mid mydriasis, narrow anterior chamber (AC) and IOP of 58 mmHg OD and 47 mmHg in OS. After systemic therapy with intravenous mannitol, oral acetazolamide and topical pilocarpine, the transparency of the cornea improved, allowing us to perform bilateral iridotomy. Later, the patient underwent Pentacam exam, OCT RNFL and Computerized Perimetry Results: After therapy, there was complete recovery of the symptoms, with stabilization of IOP at 10-12 mmHg OU. Gonioscopy revealed a narrow iridocorneal angle, grade II in Shaffer’s classification, corroborated by the Pentacam exam. The OCT showed a pathological decrease of the nerve fiber layer in the upper OD and suspicion in the upper OS. Perimetry also revealed changes in threshold sensitivity, especially in the right eye. Conclusions: We concluded this to be a case of bilateral AACG, probably induced by fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Some studies refer that there are serotonergic receptors in the iris-ciliary body complex which, once stimulated, could lead to pupil sphincter muscle relaxation. Thus, the increased serotonin levels associated with the anticholinergic effects inherent to these agents, appears to be an important factor in inducing mydriasis, triggering AACG in patients with predisposing ocular anatomy. The growing number of AACG cases associated with fluoxetine, paroxetine and venlafaxine reported in the literature in recent years, shows that may be important an ophthalmologycal exam before initiating treatment with SSRIs, to exclude a narrow angle AC in these patients.